Analysis of financial independence of ukrainian enterprises - Оksana Nuzhna (Економічний форум)
The article is devoted to practical aspects of analysing the financial independence of Ukrainian enterprises as an important component of managing their financial stability. The purpose of the study is to determine the level of their financial independence by calculating the coefficient of autonomy and to conduct a comparative analysis of the results obtained in the context of certain types of activities based on the study of the structure of sources of financial resources of enterprises in Ukraine as a whole and with a distribution by size. The information base of the study consisted of educational and methodological literature on financial analysis, monographic and dissertation research, as well as data from the state statistics service of Ukraine for 2013-2021. The objects of research are enterprises of Ukraine, enterprises of agriculture, forestry and fisheries, as well as industrial enterprises in general and with their distribution by size large, medium, small and microenterprises. The analysis showed a discrepancy between the autonomy coefficient and the recommended range of values during the entire study period for Ukrainian enterprises in general and industrial enterprises. Moreover, for industrial enterprises, a negative value of the autonomy coefficient for a group of medium and small enterprises was recorded, which indicates not only the lack of equity, but also its negative value and the complete dependence of these enterprises on external sources of financing. A much better situation is observed with financial independence for enterprises of agriculture, forestry and fisheries of Ukraine, for which the value of the coefficient of autonomy either exceeds the lower limit of the recommended range of values, or is close to reaching it. The positive dynamics of the autonomy coefficient in recent years has been established for all objects of research the enterprises of different types of activities and different sizes. The forecast is made regarding the negative impact of the war and the emergence of a whole range of risks in all spheres of activity on the level of financial independence of Ukrainian enterprises and, accordingly, the level of their financial stability